CERTAIN MECHANISMS OF SECONDARY IMMUNOSUPPRESSION UNDER CHRONISATION OF GEOHELMINTHIASIS - E. A. Grishina; A. S. Dovgalev (Российский паразитологический журнал)
The exact mechanisms of secondary immunosuppression caused by parasite infection has not yet been clarified. Even less explored is the ability of helminths antigens to induce apoptosis in immuno-competent mammalian cells during the invasion. The aim of this study was to establish the possible relationship between the immuno-competent cells apoptosis, the dynamics of changes in the leucocyte count of peripheral blood and development of immunosuppression during chronization of helminthosis in mice infected with Syphaciaobvelata.Materials and methods. Eighty five albino mice with a mean body weight of 18-20 g were used in the experiment. Animals were divided into the following experimental groups: 1) intact animals (control group), 2) animals infected Syphaciaobvelata (Rudolphi, 1802), Seurat, from 1916 n / a Oxiurata.Mice were decapitated after 1, 2, 3, 6, 7, 8 weeks after infection by raush-anesthesia and blood was collected from the tail vein. Blood smears were stained with Giemsa-Romanovsky method. Light microscopy was used to determine leukocyte formula, and to count the number of neutrophils and lymphocytes with morphological signs of varying degrees of apoptosis.Lymphocytes were isolated by Ficoll — verografin density gradient separation, their total concentration was counted in Goryaev camera and adjusted with medium to 2 x106/ml. The obtained data were statistically processed using STATISTICA software (version 8.0 for Windows) and the SPSS (version 11.0).Results and discussion. Helminthiases in the acute stage (1, 2, 3 weeks) promoted eosinophilia formation and reduction of geterofilov and lymphocytes number, while did not change significantly the percentage of other forms of white blood cells. In blood smears morphological features of apoptosis were observed in a small amount in geterofily lymphocytes.Thus, it was found that in the acute stage of infection the activation of cellular immunity occures, expressed mainly in the form of eosinophilia and indicating the development of hypersensitivity.During the 8 weeks development of helmithasis (mice syphaciosis) and its conversion into chronic stage the activity of leukocytes apoptosis increased. This is apparently an essential link in the pathogenesis of helminthiasis in general and developing immunosuppression in particular. The most important role belong to the apoptosis of immunocompetent cells such as lymphocytes and geterophyls.